2019
DOI: 10.9734/jamcs/2019/v34i3-430208
|View full text |Cite
|
Sign up to set email alerts
|

A Lomax-inverse Lindley Distribution: Model, Properties and Applications to Lifetime Data

Abstract: This article proposed a new extension of the Inverse Lindley distribution called “Lomax-Inverse Lindley distribution” which is more flexible compared to the Inverse Lindley distribution and other similar models. The paper derives and discusses some Statistical properties of the new distribution which include the limiting behavior, quantile function, reliability functions and distribution of order statistics. The parameters of the new model are estimated by method of maximum likelihood estimation. Conclusively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Besides these generalized Rayleigh distributions, some researchers have proven that most extended or compound distributions are more flexible and perform better than their standard counterparts when applied to real life datasets. For instance, the Weibull-Exponential distribution was found to perform better than the Exponential distribution (Oguntunde et al [12]), the Weibull-Frechet distribution exhibited a very higher level of flexibility when applied to real life data compared to the standard Frechet distribution (Afify et al [13]), the Lomax-Exponential distribution was also discovered to have perform better when compared to the exponential distribution during real life data analysis (Ieren and Kuhe, [14]), others are the Weibull-Lindley distribution by Ieren et al [15], the Gompertz-Lindley distribution by Koleoso et al [16], the Lomax-inverse Lindley distribution by Ieren et al [17], the transmuted Lindley-Exponential distribution by Umar et al [18], the Power Gompertz distribution by Ieren et al [19] and many others.…”
Section: Introductionmentioning
confidence: 99%
“…Besides these generalized Rayleigh distributions, some researchers have proven that most extended or compound distributions are more flexible and perform better than their standard counterparts when applied to real life datasets. For instance, the Weibull-Exponential distribution was found to perform better than the Exponential distribution (Oguntunde et al [12]), the Weibull-Frechet distribution exhibited a very higher level of flexibility when applied to real life data compared to the standard Frechet distribution (Afify et al [13]), the Lomax-Exponential distribution was also discovered to have perform better when compared to the exponential distribution during real life data analysis (Ieren and Kuhe, [14]), others are the Weibull-Lindley distribution by Ieren et al [15], the Gompertz-Lindley distribution by Koleoso et al [16], the Lomax-inverse Lindley distribution by Ieren et al [17], the transmuted Lindley-Exponential distribution by Umar et al [18], the Power Gompertz distribution by Ieren et al [19] and many others.…”
Section: Introductionmentioning
confidence: 99%
“…There are several standard probability distributions that have been used over the years for modelling real-life datasets however research has shown that most of these distributions do not adequately model some of these heavily skewed datasets and therefore creating a problem in statistical theory and applications. Recently, numerous extended or compound probability distributions have proposed in the literature for modeling real-life situations and these compound distributions are found to be skewed, flexible and more better in statistical modeling compared to their standard counterparts [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous extended or compound probability distributions have been proposed in the literature for modeling real life situations. These compound distributions are found to be skewed, flexible and much better in statistical modeling compared to their standard counterparts [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%